Pengelolaan Sumber Daya Manusia Pada Perpustakaan Universitas Islam Negeri Salatiga - Majid Kobat, Hardian; Sri Lestari, Elizabeth; Koerniawati, Tintien (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2024)
The available resources within an organization constitute the primary foundation for sustaining its existence. The role of librarians is crucial in constructing the system structure within a library. In 2018, the Library of UIN Salatiga achieved accreditation at level A. The library must continuously enhance its services, and the accomplishments attained by the library are inseparable from the human resources capital. Human resources are considered intellectual assets owned by the library. Effective human capital management is deemed essential to improve the quality of services and the capabilities of the library. The objective of this research is to understand how human resource management is conducted in the library of UIN Salatiga. The research employed a descriptive type, illustrating a phenomenon systematically and accurately regarding facts, characteristics, and relationships among the components being studied. Data collection techniques utilized questionnaires, with a population of 11 individuals in this study, employing total sampling. The research findings indicate that the Library of UIN Salatiga has effective human resource management by granting library staff permissions for early education based on the educational levels of the staff and the training attended by both librarians and non-librarian personnel. The library also emphasizes human capital by requiring library staff to participate in activities such as training, seminars, and other events supporting the development of library staff. To enhance human resource management in the Library of UIN Salatiga and maximize the educational and training experiences of the staff, creating a favorable working environment, the author suggests the following: the library head should establish a clear organizational structure. This will facilitate the allocation of tasks and responsibilities among the staff. The organizational structure serves as a guide for staff to understand their authority and responsibilities more precisely.